Verbs of Reaction in Czech and the Topic-Focus Articulation of the Sentence - Veselý, Vojtěch (Bohemica Olomucensia, 2024)
This paper examines whether the presupposition of a stimulus implied by verbs of reaction in Czech is manifested in the topic-focus articulation of the sentence, and whether it is affected by the fact that the stimulus and the reaction together form (or do not form) a reciprocal situation.
Keywords: Presupposition; Reciprocity; Stimulus; Topic-Focus Articulation; Verb of Reaction